2019
DOI: 10.3390/admsci9030054
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Country Differences in Entrepreneurial Internationalization Tendencies: Evidence from Germany and Pakistan

Abstract: Previous research has emphasized the importance of entrepreneurial characteristics for international entrepreneurship, hence the application of concepts such as entrepreneurial orientation and global mindset to the study of entrepreneurial internationalization tendencies (EIT). However, literature does not adequately address how EIT differ between countries or manifest in fragile country settings. We address this gap through a quantitative study to investigate EIT in two national settings that largely differ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…Furthermore, we found empirical evidence for the role of digital capabilities for IEI in general. Thus, we find that digital capabilities are a significant predictor of IEI, which extends findings of previous research that already highlight the role of demographic characteristics as e.g., migration background [22], institutional environments [97], attitudinal elements like international entrepreneurial orientation and a global mindset [44,97], as well as human capital and experiences [40] for IE.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we found empirical evidence for the role of digital capabilities for IEI in general. Thus, we find that digital capabilities are a significant predictor of IEI, which extends findings of previous research that already highlight the role of demographic characteristics as e.g., migration background [22], institutional environments [97], attitudinal elements like international entrepreneurial orientation and a global mindset [44,97], as well as human capital and experiences [40] for IE.…”
Section: Discussionsupporting
confidence: 88%
“…Less developed countries are facing a greater likelihood of environmental risk exposure and are at the same time dealing with little coping capacities to remove or protect from environmental damage [3]. This might be related to a lack of institutional stability and support, which has generally been found to enhance the fear of entrepreneurial failure [43].…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature produced strong evidence that entrepreneurial self-efficacy is an essential determinant of entrepreneurial intention [41,42]. Furthermore, research has shown that cognitive factors related to entrepreneurship highly depend on contextual factors [43,44]. Thus, we assume that the impact of self-efficacy on sustainable entrepreneurial intention might depend on increasing levels of environmental risk exposure.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Moon et al [133] point out the importance of building a socially and ecologically aware mindset for learners and teachers alike to maximize the sustainable impact of EET in higher education institutes. Although a large number of studies focus on mindset development as key EET outcome (for example [68,69,134,135]), very few focus on EET's relationship to developing the mindset needed to achieve sustainability through entrepreneurship. Additionally, I follow Schaltegger et al [136] in recommending additional research on the role of collaboration in achieving sustainable development through entrepreneurship, with a specific focus on EET's impact on fostering collaborative mechanisms among and within entrepreneurial ventures and teams to enhance sustainability.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%